Indigenous Peoples and Customary Law in Lolayan District, Bolaang Mongondow Regency in a Modern State - Nasir Katong; Sintya Paula Junaedy; Debby Ch. Sendow (Westscience Press, 2023)
Indigenous peoples are an orderly unity in which members are not only bound to the place of residence where a particular area, both in worldly terms as a place of life and in spiritual relations as a place of worship of ancestral spirits (territorial), but also bound to hereditary relationships in blood alliances and the same familiarity of a customary relationship (genealogical). Each indigenous community has customary Law that is used to regulate all problems that occur within the familiar environment. The second use in legislation is that indigenous peoples and customary Law are often used interchangeably in laws and regulations but lead to the same subject. Some argue that customary Law is a law left over from the past so that it is less comfortable with modern life like now, which is entering the era of modernization. Such an opinion is not wrong, but not all are true. Sayskan is right because it is recognized that customary Law is traditional, while life in the current era demands everything modern. This is not entirely true because there are several laws formed that are introduced from Customary Law. These two entities, both customary communities and Customary Law, include the same people and live on the same earth therefore, naturally, indigenous peoples also get the same rights as other countries, such as equality of public services and law enforcement. Related to the relevance of global customary Law in the global era. In the age of globalization, it is necessary to follow the pattern of becoming a peer again. Therefore, the continuity of customary Law becomes very important. Customary Law is no longer limited to indigenous Indonesian Law that must be maintained. Still, more than that, traditional Law should have a function as a